Social Anthropology Dissertation Photographs 2017 - Arnarsdóttir, Hörn; Dailly, Damon; Bolton, Becca (re:think - a journal of creative ethnography, 2018)
A collection of photographs submitted to the Social Anthropology Undergraduate Dissertation Photo Competition 2017 complete with short reflections and commentary from authors.